ChemInform Abstract: Mitsunobu Cyclodehydration of N‐Pivaloyl‐2‐aminophenethyl Alcohol for Asymmetric Synthesis of trans‐2, 3‐Disubstituted Indolines. Issue 32 (18th July 2013) - Kang, Kyoung Hee; Kim, Yelim; Im, Chan; Park, Yong Sun
Abstract The access to the other enantiomer can be easily achieved by using (+)‐sparteine.